Oxford School Dictionary & Thesaurus - Edited by Allen, Robert (Oxford Oxford University Press, 2012)
The Oxford School Dictionary and Thesaurus combines a comprehensive dictionary at the top of the page with a companion thesaurus at the bottom, for the upper primary student moving into secondary school. The dictionary contains clear simple definitions, up-to-date example sentences, and support on spelling, grammar and punctuation. The thesaurus provides thousands of up-to-date synonyms, arranged by the meaning that.
Keywords: English Language